Using textbooks in the mathematics classroom – the teachers’ view - Lepik, Madis; Grevholm, Barbro; Viholainen, Antti (NOMAD Nordic Studies in Mathematics Education, 2015)
Mathematics teachers’ self-reported practices of textbook use were investigated by a survey of more than 400 teachers in Estonia, Finland and Norway. Do they have different approaches in their use of textbooks and to what extent do they rely on textbooks in planning and preparing their lessons? What kinds of patterns characterize teachers’ practice when using textbooks in mathematics lessons? The answers to these questions indicate that in Estonia and Finland teachers have similar attitudes towards textbooks. They are responsible for the choice of book and the textbook has a strong effect on their didactical choices. In Norway the teachers are less dependent on the textbook. In Finland the textbook is the crucial resource for exercises while in Estonia and Norway teachers use other resources more often. The study reveals the limited use of the full potential of the textbook. Almost 45 % of the teachers use the textbook simply as an exercise book. As a result the pupils do not get the opportunity to fully exploit the book as a multifaceted learning resource.